2019
DOI: 10.1128/jvi.01893-18
|View full text |Cite
|
Sign up to set email alerts
|

Correction for Wood et al., “Enhancer Control of MicroRNA miR-155 Expression in Epstein-Barr Virus-Infected B Cells”

Abstract: Page 5, Fig. 2D: Due to errors in final figure assembly, the actin loading control blots were placed in the incorrect positions under the left and right sections. The right-hand blot should be on the left, and the left-hand blot should be on the right.Figure 2D should appear as shown below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that enhancers can recruit TFs to positively promote target gene expression, and consequently cause HCC tumorigenesis [5]. Recent studies showed that enhancers (including typical enhancers and super enhancers) can regulate miRNA expression and participate in the biological synthesis by regulating Drosha/DGCR8 [6,7]. However, whether the regulatory network is formed by TEAD1, enhancer and microRNA and whether the regulatory network is involved in the regulation of HCC are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that enhancers can recruit TFs to positively promote target gene expression, and consequently cause HCC tumorigenesis [5]. Recent studies showed that enhancers (including typical enhancers and super enhancers) can regulate miRNA expression and participate in the biological synthesis by regulating Drosha/DGCR8 [6,7]. However, whether the regulatory network is formed by TEAD1, enhancer and microRNA and whether the regulatory network is involved in the regulation of HCC are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that miR-24-1, which is present in the nucleus, promotes gene expression by targeting enhancers, suggesting that there is an obvious interaction between enhancers and miRNAs ( Xiao et al, 2017 ). Other recent studies showed that enhancers (including typical enhancers and super enhancers) are found to regulate miRNA expression and participate in the biological synthesis of miRNAs regulated by Drosha/DGCR8 ( Yun et al, 2018 ; Wood et al, 2019 ). These studies suggested that enhancers are involved in miRNA regulatory networks and contribute greatly to tumorigenesis and development.…”
Section: Introductionmentioning
confidence: 99%